The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s13197-014-1698-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiations and biodegradation techniques for detoxifying Carica papaya seed oil for effective dietary and industrial use

Abstract: Benzyl isothiocyanate (BITC) is toxic in high concentration. The capacity of Aspergillus niger, microwave and ultraviolet radiations to reduce the BITC levels in Carica papaya Linn seed oil were assessed in vitro. BITC at different concentrations were periodically exposed to microwave and ultraviolet radiations for 30 min and 10 h, respectively; and to identify Aspergillus niger for 4 days. Microwave radiation significantly reduced (p<0.05) BITC levels (0.0272, 0.0544, and 0.0816 μmol) to 12.19, 8.99 and 27.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A recent study reported reduction of BITC levels in raw papaya seed oil by treatment with Aspergillus niger , microwave, or ultraviolet radiations. 35 While these treatments were reported to lower the BITC they may also affect the quality of the oil with fungal spores or metabolites, or may be prohibitive in large scale, requiring high energy or capital cost.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported reduction of BITC levels in raw papaya seed oil by treatment with Aspergillus niger , microwave, or ultraviolet radiations. 35 While these treatments were reported to lower the BITC they may also affect the quality of the oil with fungal spores or metabolites, or may be prohibitive in large scale, requiring high energy or capital cost.…”
Section: Resultsmentioning
confidence: 99%
“…There is no need to rely on costly means (such as thermal deactivation) to deactivate the myrosinase enzyme in the seeds prior to milling and oil extraction, or to detoxify the seed oil by chemical, physical, or biological methods, as reported in other studies. 35 …”
Section: Resultsmentioning
confidence: 99%
“…Similar increase in weight due to the 30 days intraperitoneal administration of methanolic extract from A. pavonina was previously reported ( 31 ). The favorable growth may be due to reduction or detoxification of potential toxic compound(s) in the seeds by the combined microwaving and the 48 h soaking induced fermentation process during the production of the pro-milk extracts ( 1 , 69 , 70 ). It is further suggested that LD50 and the histopathological studies be carried out on the pro-milk extract for A. pavonina seed.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies, such as transforming the current underutilized and/or poisonous plant resource to their edible forms and biotransforming the present waste to nutrients or sources of nutrients, are required to meet the nutritional needs of the increasing global population ( 1 ). Plants had largely been useful for ages as a source of nourishing substances.…”
Section: Introductionmentioning
confidence: 99%
“…Many surfaces, including oilseeds become infested; therefore, it is a requirement for effective disinfestations (Christofi et al, 2008). In this line, Afolabi et al, (2015) stated that microwave radiation could detoxify seed oil and improve its dietary and industrial use. Organisms under microwave's irradiation are prone to some types of stress such as controlled atmosphere and cold ambient (Wang and Tang, 2001).…”
Section: Introductionmentioning
confidence: 99%